Rubber particle self-compacting concrete

By modifying the rubber particles, a pre-crosslinked structure is formed, which solves the negative impact of rubber particles on strength when added to concrete, and significantly improves the compressive, split and bending properties of concrete, achieving the best balance of performance.

CN119661133APending Publication Date: 2025-03-21ZHEJIANG COMM CONSTR GRP CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411833386.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-13
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

In the prior art, when rubber particles are added to concrete, it may negatively affect the strength of the concrete, resulting in reduced compression, split and bending performance, and difficult to achieve optimal performance balance.

Method used

By adjusting the amount of rubber particles in the concrete and modifying the rubber particles, it includes preheating the rubber powder in a closed environment, adding epithelium catechol ester dispersion for activation, then adding benzoyl peroxide, toluenesulfonamide/epoxy resin and ammonium molybdate, and stirring at high temperature to form a pre-crosslinked structure to improve the toughness and strength of the rubber particles.

Benefits of technology

The compressive, split and bending properties of concrete are significantly improved, the negative impact of rubber particles on concrete strength is reduced, and the physical and chemical properties of concrete are optimized.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to rubber particle self-compacting concrete which comprises 400.00-580.00 kg / m of a cementing material, 1781.00-1831.00 kg / m of aggregate, modified rubber powder accounting for 18.50-20.00% of the total weight of the aggregate, water accounting for 22.41-39.00% of the total weight of the cementing material, and a polycarboxylic acid additive accounting for 1.08-2.93% of the total weight of the cementing material, wherein the modification process of the modified rubber powder comprises the following steps: in a closed environment, preheating waste rubber powder, adding the preheated waste rubber powder into epigallocatechin gallate dispersion liquid, soaking and activating for 20-40 minutes, then adding benzoyl peroxide, toluene sulfonamide / epoxy resin and ammonium molybdate, stirring and modifying for 10-12 hours at 160-180 DEG C, and after the modification is finished, performing post-treatment to obtain the modified rubber powder. The modified rubber powder is obtained. The mixing amount of the rubber particles in the concrete is adjusted, and the rubber particles are properly modified, so that the concrete has the advantage of jointly improving the compression resistance, splitting tensile property and bending tensile property of the concrete.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of self-compacting concrete, in particular to a self-compacting concrete with rubber particles. Background Art

[0002] The treatment of waste rubber tires has become a major environmental issue. It is estimated that 1.5 billion tires are produced worldwide each year. Millions of tires are discarded or landfilled around the world each year, posing a serious threat to the ecological environment. It is estimated that nearly 1 billion tires exceed their service life each year, and more than 50% of the waste tires are discarded without any treatment. It is estimated that by 2030, the number of waste tires discarded each year will reach 1.2 billion. If the accumulated waste tires are taken into account, the number will reach 5 billion. According to production data from the Rubber Manufacturing Association, more than 230 million waste tires were produced in the United States each year around 2016, and about 75 million of the waste would be accumulated. According to the China Rubber Industry Association, the amount of waste tires produced in my country in 2017 exceeded 350 million, weighing about 12.7 million tons. Only 18% of the recycled waste tires are reprocessed and reused, while 38% are idle and 40% of the waste tires are incinerated as energy materials. These statistics show that recycling waste tires has considerable economic value.

[0003] Regarding the application of rubber in concrete, Eldin and Senouci tested the compressive and tensile strengths of rubber concrete in which part of the aggregate was replaced by tire pieces or crushed particles. The results showed that when the crushed stone was completely replaced by rubber aggregate, the compressive strength and tensile strength could be reduced to 85% and 50% of the control ordinary concrete, respectively. Compared with crushed stone replacement, the loss of compressive strength of concrete replaced by manufactured sand was smaller, and the strength was about 65% of the compressive strength of concrete without rubber. Bayomy and Khatib replaced the manufactured sand and crushed stone in concrete with two types of tire rubber, respectively. Three groups of samples were prepared in the test, including fine rubber particles replacing manufactured sand, coarse rubber strips replacing crushed stone, and crushed stone and manufactured sand being partially replaced by equal volumes at the same time. The rubber content of each group ranged from 5% to 100%. They found that when the rubber content reached 40%, the slump was close to zero and the concrete could not be mixed manually. They also found that the air content in rubber concrete was higher than that of ordinary concrete without rubber because the rough surface of rubber particles could introduce air when the concrete was mixed. The results show that the higher the rubber content in concrete, the greater the loss rate of compressive strength of concrete. When the rubber content exceeds 60% of the total volume of aggregate, the compressive strength is reduced to 10% of the concrete without rubber. Topcu et al. studied the effect of coarse and fine rubber particle size on concrete strength through experiments. The test results show that compared with the benchmark concrete, the compressive strength of annular and cylindrical concrete specimens with fine rubber particles decreased by 50%, and the splitting tensile strength decreased by 64%; the compressive strength of annular and cylindrical concrete specimens with coarse rubber particles decreased by 80%, and the splitting tensile strength decreased by 74%. Onuaguluchi and Panesar observed that alkali washing of rubber and the addition of silica fume can effectively improve the compressive strength of rubber concrete. Youssf et al. mentioned that when waste rubber replaced aggregate at a substitution rate of 3.5%, the addition of rubber had no significant effect on the compressive strength of concrete. Compared with untreated rubber particles, the compressive strength of rubber concrete prepared by incorporating NaOH-treated rubber particles increased by 15% at 28 days.

[0004] Currently, Ganjian et al. investigated the properties of rubber concrete by replacing aggregate and cement with different volumetric amounts of rubber. They prepared two groups of samples in their experiments. In both groups, the crushed stone and cement of the concrete were replaced by different proportions of rubber particles and waste rubber powder, respectively. The results showed that when only 5% of the aggregate or cement in the concrete was replaced by rubber, the reduction in compressive strength was negligible. At higher amounts (7.5% and 10%), the loss of compressive strength was significant. In particular, the loss of compressive strength of the samples where cement was replaced by rubber powder was much greater than that of the samples where the aggregate was replaced by an equal volume of rubber particles. In addition, the tensile and flexural strengths also decreased significantly with the increase in the rubber content in the concrete. Dong et al. studied the properties of concrete after the incorporation of untreated rubber and rubber coated with a silane coupling agent into concrete. It was observed that the compressive strength of the coated rubber concrete was significantly improved due to better chemical bonding and improved interfaces around the rubber particles. The study found that the lower stiffness loss of rubber self-compacting concrete compared to ordinary rubber concrete can be clearly attributed to its improved microstructure due to improved contact in the interface transition zone. The test showed that the toughness of rubber concrete was greater than that of ordinary concrete due to its higher post-peak reaction, but the reduction in peak load led to a reduction in fracture energy. Rubber concrete was also found to have greater ductility than ordinary concrete because the higher peak strain allowed for greater plastic deformation before the yield point. According to Zheng's research, due to the higher ductility of rubber concrete (using rubber strips) than ordinary concrete, its brittleness index (BI) was lower than that of ordinary concrete, and the BI of concrete with the addition of rubber strips decreased faster with the rubber content than with rubber particles.

[0005] It is not difficult to see from the above research results that by adding rubber particles to concrete, the crack resistance, impact resistance, damping performance, and deformation capacity of concrete in prefabricated bridge projects can be effectively enhanced, while also improving its sound insulation and thermal insulation effects. This not only helps to increase the recycling rate of waste tires, but also brings more environmental benefits to bridge projects. However, in practical applications, the addition of rubber particles may have a certain negative impact on the strength of concrete. Therefore, how to determine an appropriate amount of rubber particles and appropriately modify the rubber particles to ensure that the various properties of concrete achieve the best balance has become a key technical problem that needs to be solved urgently. Summary of the invention

[0006] The problem to be solved by the present invention is to provide a rubber particle self-compacting concrete in view of the above-mentioned deficiencies existing in the prior art. By adjusting the amount of rubber particles in the concrete and appropriately modifying the rubber particles, the compression, splitting and flexural properties of the concrete are improved.

[0007] The above-mentioned object of the present invention is achieved through the following technical solutions: A rubber particle self-compacting concrete comprises 400.00-580.00 kg / m³ of cementitious material, 1781.00-1831.00 kg / m³ of aggregate, modified rubber powder accounting for 18.50-20.00% of the total weight of the aggregate, water accounting for 22.41-39.00% of the total weight of the cementitious material, and a polycarboxylic acid admixture accounting for 1.08-2.93% of the total weight of the cementitious material; wherein the modification process of the modified rubber powder comprises: in a closed environment, after preheating the waste rubber powder, adding it into a dispersion of epigallocatechin gallate for immersion activation for 20-40 minutes, then adding benzoyl peroxide, toluenesulfonamide / epoxy resin, and ammonium molybdate, stirring and modifying at 160-180°C for 10-12 hours, and after the modification is completed, post-processing is performed to obtain the modified rubber powder.

[0008] Furthermore, the cementitious material includes 160.00-442.00 kg / m³ cement, 80.00-94.00 kg / m³ mineral powder, and 54.00-160.00 kg / m³ fly ash.

[0009] Furthermore, the fly ash accounts for 9.31-40.00% (fly ash replacement rate) of the total weight of the cementitious material.

[0010] Furthermore, the aggregate includes 84.00~158.00kg / m³ of river sand with a particle size of less than 5mm, 598.00.00~755.00kg / m³ of machine-made sand, 788.00.00~826.00kg / m³ of large crushed stone with a particle size of 10~20mm, and 197.00~207.00kg / m³ of small crushed stone with a particle size of less than 10mm.

[0011] Furthermore, the river sand and machine-made sand account for 42.00-46.00% (sand ratio) of the total weight of the aggregate.

[0012] Furthermore, the machine-made sand accounts for 79.95-89.99% (machine-made sand replacement rate) of the total weight of the river sand and the machine-made sand.

[0013] Furthermore, the mass ratio of the large gravel to the small gravel is 3.99-4.01.

[0014] Furthermore, the large gravel and the small gravel are made of limestone.

[0015] Furthermore, during the modification process of the modified rubber powder, the preheating temperature of the waste rubber powder is controlled to be 50-90° C. and the preheating time is controlled to be 30-60 min.

[0016] Furthermore, during the modification process of the modified rubber powder, the volume ratio of the waste rubber powder to the epigallocatechin gallate dispersion is controlled to be 1:5-10.

[0017] Furthermore, during the modification process of the modified rubber powder, the concentration of the epigallocatechin gallate dispersion is controlled to be 0.08-0.12 kg / m³.

[0018] Furthermore, during the modification process of the modified rubber powder, the mass ratio of the waste rubber powder, benzoyl peroxide, toluenesulfonamide / epoxy resin, and ammonium molybdate is controlled to be 100:32-38:20-25:2-5.

[0019] In summary, the beneficial technical effects of the present invention are as follows: in the modification process of the modified rubber powder, the surface of the rubber powder is firstly pretreated by medium temperature preheating. The treatment at this stage effectively removes the oil and impurities on the surface of the waste rubber powder, and significantly reduces the surface cracks and roughness, laying a good foundation for subsequent treatment; then, epigallocatechin gallate is used to activate the surface of the rubber powder by washing and soaking, which not only significantly improves the bonding strength between the rubber powder and the cementitious material, but also effectively enhances the toughness and strength of the rubber powder. It effectively prevents the aging and deformation of the rubber powder. On this basis, by introducing benzoyl peroxide and toluenesulfonamide / epoxy resin and carrying out high-temperature modification under the catalysis of ammonium molybdate, a pre-crosslinked structure is formed between the rubber molecules. This pre-crosslinked structure can achieve a tighter vulcanization crosslinking during the concrete mixing process, so that the rubber particles can be more evenly dispersed in the aggregate framework, and the surface softness of the rubber powder is reduced, which further optimizes the physical and chemical properties of the concrete, so that the rubber particle self-compacting concrete exhibits more superior compression, splitting and flexural properties. DETAILED DESCRIPTION

[0020] In order to make the technical means, creative features, objectives and functions achieved by the present invention clearer and easier to understand, the present invention is further explained below in conjunction with specific implementation methods.

[0021] Example 1: A rubber particle self-compacting concrete disclosed in the present invention includes 400.00 kg / m³ cementitious material, 11824.00 kg / m³ aggregate, 345.00 kg / m³ modified rubber powder, 156.00 kg / m³ water, and 4.30 kg / m³ polycarboxylic acid admixture; wherein, The cementitious materials include 160.00kg / m³ cement, 80.00kg / m³ mineral powder, and 160.00kg / m³ fly ash; Aggregates include 84.00kg / m³ river sand with a particle size below 5mm, 755.00kg / m³ machine-made sand, 788.00kg / m³ large crushed stone with a particle size of 10~20mm, and 197.00kg / m³ small crushed stone with a particle size below 10mm. The crushed stone of large and small crushed stone is limestone.

[0022] The specific implementation method of rubber particle self-compacting concrete is: S1 In a closed environment, the waste rubber powder is preheated at 75°C for 45 minutes, and then added into 0.10kg / m³ epigallocatechol gallate dispersion for immersion activation for 30 minutes, and the volume ratio of the waste rubber powder to the epigallocatechol gallate dispersion is controlled to be 1:8, and then benzoyl peroxide, toluenesulfonamide / epoxy resin, and ammonium molybdate are added, and the mass ratio of the waste rubber powder, benzoyl peroxide, toluenesulfonamide / epoxy resin, and ammonium molybdate is controlled to be 100:36:22:3, and the modified rubber powder is obtained by stirring at 175°C for 10 hours. After the modification is completed, the modified rubber powder is obtained by post-treatment; S2 first adds aggregate and modified rubber powder obtained in S1 into the mixer, mixes for 1 minute, then adds half of the water, mixes for 2 minutes, then adds cementitious material, polycarboxylic acid admixture and the remaining water by the same mixing method, wet mixes for 3 minutes, until the mixture is evenly dispersed; S3 adds the mixture obtained in S2 into the test mold in layers and batches, vibrates and compacts it, demolds it after 20 hours of molding, and performs curing to obtain the rubber particle self-compacting concrete.

[0023] In the early stage of the research, the present invention accurately evaluated the toughness of rubber concrete by using the improved DPT (Double Punch Test) method, studied the influence of rubber particle dosage on the fracture toughness of concrete by using the three-point bending test under different cyclic loading conditions, and used the acoustic emission technology to test the acoustic emission characteristics of the fracture process zone of the specimen. In addition, the dynamic compression, splitting tension and bending tension properties of rubber self-compacting concrete and ordinary rubber concrete were studied by using the Hopkinson bar (SHPB) device, thereby obtaining the above-mentioned rubber particle self-compacting concrete.

[0024] According to the test, the 28d compressive strength of the rubber particle self-compacting concrete is 45.45MPa, the splitting tensile strength is 3.64MPa, and the flexural strength is 5.75MPa.

[0025] Example 2: A rubber particle self-compacting concrete disclosed in the present invention, which is different from Example 1 in that it includes 440.00 kg / m³ cementitious material, 11798.00 kg / m³ aggregate, 350.00 kg / m³ modified rubber powder, 152.00 kg / m³ water, and 5.10 kg / m³ polycarboxylic acid admixture; wherein, The cementitious materials include 266.00kg / m³ cement, 87.00kg / m³ mineral powder, and 87.00kg / m³ fly ash; Aggregates include 158.00kg / m³ river sand with a particle size below 5mm, 633.00kg / m³ machine-made sand, 806.00kg / m³ large crushed stone with a particle size between 10 and 201.00kg / m³ small crushed stone with a particle size below 10mm. The crushed stone of large and small crushed stone is limestone.

[0026] According to the test, the 28d compressive strength of rubber particle self-compacting concrete is 54.87MPa, the splitting tensile strength is 4.39MPa, and the flexural strength is 6.78MPa.

[0027] Example 3: A rubber particle self-compacting concrete disclosed in the present invention, which is different from Example 1 in that it includes 479.00 kg / m³ cementitious material, 11781.00 kg / m³ aggregate, 330.00 kg / m³ modified rubber powder, 150.00 kg / m³ water, and 5.30 kg / m³ polycarboxylic acid admixture; wherein, The cementitious materials include 244.00kg / m³ cement, 94.00kg / m³ mineral powder, and 141.00kg / m³ fly ash; Aggregates include 150.00kg / m³ river sand with a particle size below 5mm, 598.00kg / m³ machine-made sand, 826.00kg / m³ large crushed stone with a particle size between 10 and 207.00kg / m³ small crushed stone with a particle size below 10mm. The crushed stone of large and small crushed stone is limestone.

[0028] According to the test, the 28d compressive strength of rubber particle self-compacting concrete is 66.27MPa, the splitting tensile strength is 5.30MPa, and the flexural strength is 7.99MPa.

[0029] Example 4: A rubber particle self-compacting concrete disclosed in the present invention, which is different from Example 1 in that it includes 580.00 kg / m³ cementitious material, 11831.00 kg / m³ aggregate, 366.00 kg / m³ modified rubber powder, 130.00 kg / m³ water, and 17.00 kg / m³ polycarboxylic acid admixture; wherein, The cementitious materials include 442.00kg / m³ cement, 84.00kg / m³ mineral powder, and 54.00kg / m³ fly ash; Aggregates include 128.00kg / m³ river sand with a particle size below 5mm, 698.00kg / m³ machine-made sand, 804.00kg / m³ large crushed stone with a particle size between 10 and 201.00kg / m³ small crushed stone with a particle size below 10mm. The crushed stone of large and small crushed stone is limestone.

[0030] According to the test, the 28d compressive strength of the rubber particle self-compacting concrete is 83.99MPa, the splitting tensile strength is 6.72MPa, and the flexural strength is 9.82MPa.

[0031] Example 5 is a rubber particle self-compacting concrete disclosed in the present invention. The difference from Example 1 is that the specific implementation method of the rubber particle self-compacting concrete is: S1 In a closed environment, the waste rubber powder is preheated at 50°C for 30 minutes, and then added into 0.08kg / m³ epigallocatechol gallate dispersion for immersion activation for 20 minutes, and the volume ratio of the waste rubber powder to the epigallocatechol gallate dispersion is controlled to be 1:5, and then benzoyl peroxide, toluenesulfonamide / epoxy resin, and ammonium molybdate are added, and the mass ratio of the waste rubber powder, benzoyl peroxide, toluenesulfonamide / epoxy resin, and ammonium molybdate is controlled to be 100:32:20:2, and the modified rubber powder is obtained by stirring at 160°C for 10 hours. After the modification is completed, the modified rubber powder is obtained by post-treatment; S2 first adds aggregate and modified rubber powder obtained in S1 into the mixer, mixes for 1 minute, then adds half of the water, mixes for 2 minutes, then adds cementitious material, polycarboxylic acid admixture and the remaining water by the same mixing method, wet mixes for 3 minutes, until the mixture is evenly dispersed; S3 adds the mixture obtained in S2 into the test mold in layers and batches, vibrates and compacts it, demolds it after 20 hours of molding, and performs curing to obtain the rubber particle self-compacting concrete.

[0032] According to the test, the 28d compressive strength of the rubber particle self-compacting concrete is 46.30MPa, the splitting tensile strength is 3.70MPa, and the flexural strength is 5.84MPa.

[0033] Example 6: A rubber particle self-compacting concrete disclosed in the present invention, which is different from Example 1 in that the specific implementation method of the rubber particle self-compacting concrete is: S1 In a closed environment, the waste rubber powder was preheated at 60℃ for 40min, then added into 0.09kg / m³ epigallocatechol gallate dispersion for immersion activation for 25min, the volume ratio of the waste rubber powder and epigallocatechol gallate dispersion was controlled to be 1:6, benzoyl peroxide, toluenesulfonamide / epoxy resin, and ammonium molybdate were added, the mass ratio of the waste rubber powder, benzoyl peroxide, toluenesulfonamide / epoxy resin, and ammonium molybdate was controlled to be 100:34:21:3, and the modified rubber powder was obtained by stirring at 165℃ for 11h. After the modification, the modified rubber powder was obtained by post-treatment. S2 first adds aggregate and modified rubber powder obtained in S1 into the mixer, mixes for 1 minute, then adds half of the water, mixes for 2 minutes, then adds cementitious material, polycarboxylic acid admixture and the remaining water by the same mixing method, wet mixes for 3 minutes, until the mixture is evenly dispersed; S3 adds the mixture obtained in S2 into the test mold in layers and batches, vibrates and compacts it, demolds it after 20 hours of molding, and performs curing to obtain the rubber particle self-compacting concrete.

[0034] According to the test, the 28d compressive strength of the rubber particle self-compacting concrete is 42.84MPa, the splitting tensile strength is 3.43MPa, and the flexural strength is 5.46MPa.

[0035] Example 7 is a rubber particle self-compacting concrete disclosed in the present invention. The difference from Example 1 is that the specific implementation method of the rubber particle self-compacting concrete is: S1 In a closed environment, the waste rubber powder is preheated at 80°C for 50 minutes, and then added into 0.11kg / m³ epigallocatechol gallate dispersion for immersion activation for 35 minutes, and the volume ratio of the waste rubber powder to the epigallocatechol gallate dispersion is controlled to be 1:9, and then benzoyl peroxide, toluenesulfonamide / epoxy resin, and ammonium molybdate are added, and the mass ratio of the waste rubber powder, benzoyl peroxide, toluenesulfonamide / epoxy resin, and ammonium molybdate is controlled to be 100:35:23:4, and the modified rubber powder is obtained by stirring at 170°C for 12 hours. After the modification is completed, the modified rubber powder is obtained by post-treatment; S2 first adds aggregate and modified rubber powder obtained in S1 into the mixer, mixes for 1 minute, then adds half of the water, mixes for 2 minutes, then adds cementitious material, polycarboxylic acid admixture and the remaining water by the same mixing method, wet mixes for 3 minutes, until the mixture is evenly dispersed; S3 adds the mixture obtained in S2 into the test mold in layers and batches, vibrates and compacts it, demolds it after 20 hours of molding, and performs curing to obtain the rubber particle self-compacting concrete.

[0036] According to the test, the 28d compressive strength of the rubber particle self-compacting concrete is 43.21MPa, the splitting tensile strength is 3.46MPa, and the flexural strength is 5.50MPa.

[0037] Example 8 is a rubber particle self-compacting concrete disclosed in the present invention. The difference from Example 1 is that the specific implementation method of the rubber particle self-compacting concrete is: S1 In a closed environment, the waste rubber powder is preheated at 90°C for 60 minutes, and then added into 0.12kg / m³ epigallocatechol gallate dispersion for immersion activation for 40 minutes, and the volume ratio of the waste rubber powder to the epigallocatechol gallate dispersion is controlled to be 1:10. Benzoyl peroxide, toluenesulfonamide / epoxy resin, and ammonium molybdate are then added, and the mass ratio of the waste rubber powder, benzoyl peroxide, toluenesulfonamide / epoxy resin, and ammonium molybdate is controlled to be 100:38:25:5, and the mixture is stirred and modified at 180°C for 12 hours. After the modification is completed, the modified rubber powder is obtained by post-treatment; S2 first adds aggregate and modified rubber powder obtained in S1 into the mixer, mixes for 1 minute, then adds half of the water, mixes for 2 minutes, then adds cementitious material, polycarboxylic acid admixture and the remaining water by the same mixing method, wet mixes for 3 minutes, until the mixture is evenly dispersed; S3 adds the mixture obtained in S2 into the test mold in layers and batches, vibrates and compacts it, demolds it after 20 hours of molding, and performs curing to obtain the rubber particle self-compacting concrete.

[0038] According to the test, the 28d compressive strength of the rubber particle self-compacting concrete is 47.55MPa, the splitting tensile strength is 3.80MPa, and the flexural strength is 5.98MPa.

[0039] Comparative Example 1 is a rubber particle self-compacting concrete disclosed in the present invention, which is different from Example 1 in that the waste rubber powder is not preheated.

[0040] According to the test, the 28d compressive strength of the rubber particle self-compacting concrete is 30.20MPa, the splitting tensile strength is 2.42MPa, and the flexural strength is 4.08MPa.

[0041] Comparative Example 2 is a rubber particle self-compacting concrete disclosed in the present invention, which is different from Example 1 in that epigallocatechin gallate is not used.

[0042] According to the test, the 28d compressive strength of the rubber particle self-compacting concrete is 21.65MPa, the splitting tensile strength is 1.99MPa, and the flexural strength is 3.46MPa.

[0043] Comparative Example 3 is a rubber particle self-compacting concrete disclosed in the present invention, which is different from Example 1 in that benzoyl peroxide, toluenesulfonamide / epoxy resin, and ammonium molybdate are not used.

[0044] According to the test, the 28d compressive strength of the rubber particle self-compacting concrete is 24.88MPa, the splitting tensile strength is 1.73MPa, and the flexural strength is 2.58MPa.

[0045] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the purpose and scope of the technical solution of the present invention, which should be included in the scope of the claims of the present invention.

Claims

1. A rubber particle self-compacting concrete, characterized in that: The invention comprises 400.00-580.00 kg / m³ of cementitious material, 1781.00-1831.00 kg / m³ of aggregate, modified rubber powder accounting for 18.50-20.00% of the total weight of the aggregate, water accounting for 22.41-39.00% of the total weight of the cementitious material, and a polycarboxylic acid admixture accounting for 1.08-2.93% of the total weight of the cementitious material; wherein the modification process of the modified rubber powder comprises: in a closed environment, preheating the waste rubber powder, adding it into a dispersion of epigallocatechin gallate for immersion activation for 20-40 minutes, then adding benzoyl peroxide, toluenesulfonamide / epoxy resin, and ammonium molybdate, stirring and modifying at 160-180°C for 10-12 hours, and obtaining the modified rubber powder through post-treatment after the modification.

2. The rubber particle self-compacting concrete according to claim 1, characterized in that: The cementitious material includes 160.00-442.00 kg / m³ cement, 80.00-94.00 kg / m³ mineral powder, and 54.00-160.00 kg / m³ fly ash.

3. The rubber particle self-compacting concrete according to claim 2, characterized in that: The fly ash accounts for 9.31-40.00% of the total weight of the cementitious material.

4. The rubber particle self-compacting concrete according to claim 1, characterized in that: The aggregate includes 84.00~158.00kg / m³ of river sand with a particle size below 5mm, 598.00~755.00kg / m³ of machine-made sand, 788.00~826.00kg / m³ of large crushed stone with a particle size between 10~20mm, and 197.00~207.00kg / m³ of small crushed stone with a particle size below 10mm.

5. The rubber particle self-compacting concrete according to claim 4, characterized in that: The river sand and machine-made sand account for 42.00-46.00% of the total weight of the aggregate, and the machine-made sand accounts for 79.95-89.99% of the total weight of the river sand and machine-made sand.

6. The rubber particle self-compacting concrete according to claim 4, characterized in that: The mass ratio of the large gravel to the small gravel is 3.99-4.01, and the gravel of the large gravel and the small gravel is limestone.

7. The rubber particle self-compacting concrete according to claim 1, characterized in that: During the modification process of the modified rubber powder, the preheating temperature of the waste rubber powder is controlled to be 50-90° C. and the preheating time is controlled to be 30-60 minutes.

8. The rubber particle self-compacting concrete according to claim 1, characterized in that: During the modification process of the modified rubber powder, the volume ratio of the waste rubber powder to the epigallocatechin gallate dispersion is controlled to be 1:5-10.

9. The rubber particle self-compacting concrete according to claim 8, characterized in that: During the modification process of the modified rubber powder, the concentration of the epigallocatechin gallate dispersion is controlled to be 0.08-0.12 kg / m³.

10. The rubber particle self-compacting concrete according to claim 1, characterized in that: During the modification process of the modified rubber powder, the mass ratio of the waste rubber powder, benzoyl peroxide, toluenesulfonamide / epoxy resin, and ammonium molybdate is controlled to be 100:32-38:20-25:2-5.